Memories of Shame Experiences with Others and Depression Symptoms: The Mediating Role of Experiential Avoidance. (23rd July 2013) - Carvalho, Sérgio; Dinis, Alexandra; Pinto‐Gouveia, José; Estanqueiro, Cátia
<x xml:space="preserve">Abstract</x> Background Shame experiences have been suggested to be related with psychopathological symptoms and with self‐relevant beliefs. Recent studies also suggest that avoidant‐focused strategies (e.g., rumination, thought suppression and dissociation) mediate the impact of shame memories and depression symptoms. However, experiential avoidance has been found to mediate the relation between early experience of abuse and psychopathological symptoms. Our goal was to test the mediating effect of experiential avoidance in the relation between both the nature of shame experiences at the hands of caregivers and the centrality of shame memories with others, and depression symptoms. Method Using structural equation modelling, we assessed the frequency and nature of recalled shame experiences at the hands of caregivers, the centrality of shame experiences with others throughout childhood and adolescence, experiential avoidance and depression symptomatology in 161 participants from general population. Results Experiential avoidance mediates the impact of shame experiences with caregivers and depression symptoms. Experiential avoidance also mediated the association between the centrality of shame experiences with others and depression symptoms. Conclusion Our results suggest that shame memories with others do not per se impact on depression symptoms, but rather the unwillingness to experience them and the attempts to control them. Hence, our results emphasize the importance of addressing affect regulation processes such as avoidance when dealing with shame memories, particularly with patients who experience depression symptoms. Key Practitioner Message The recall of shame experiences with caregivers is associated with the experience of depression symptoms, even when these experiences are not perceived as central points to one's life identity and story. This seems to suggest a necessity to explore these experiences in a therapeutic setting. Our findings suggest that experiential avoidance is a key process through which these memories of shame experiences impact on depression symptomatology. Hence, it seems to be of great importance to reduce experiential avoidance and help people change the way they relate with these memories. Copyright © 2013 John Wiley & Sons, Ltd.